Network analysis of illness perception, stigma, and resilience with cognition in old people living with HIV - Fan, Yunzhe; Yu, Bin; Liu, Hongyun; Ma, Hua; Ma, Chunlan; Li, Yuchen; Feng, Chuanteng; Jia, Peng; Yang, Shujuan (Journal of psychosomatic research, 2024)
Old people living with HIV (PLWH) are highly susceptible to HIV-related psychological and neurocognitive disorders, which are multidimensional and inseparably intertwined. Despite this, few studies have investigated the interrelationship between these disorders. We aimed to estimate the detailed associations and identify potential intervention points between HIV-related psychological factors and cognitive function in old PLWH. This cross-sectional study drew on the Older People with HIV Infections Cohort from 65 communities in Sichuan, China. Three HIV-related psychological factors, including illness perception, HIV stigma perception and resilience, were collected using a self-reported questionnaire. Cognitive function was measured using the MoCA-B scale. Network analysis was used to estimate the interrelationships between HIV-related psychological factors and cognitive function dimensions in old PLWH, and to identify factors that act as bridges in connecting these factors in the network. Of the 1587 old PLWH, 47.0% had mild or severe cognitive function impairment. Network analysis revealed that better visual perception was directly connected with poorer negative self-image (edge weight: 0.13), and poorer illness comprehensibility was connected with poor visual perception (−0.09) and executive functioning (−0.13). The cognitive illness perceptions (bridge strength: 0.41), illness comprehensibility (0.36) and negative self-image (0.39) were identified as bridges connecting HIV-related psychological and cognitive function. The interconnection of HIV-related illness perception, stigma perception, and resilience with cognition may be achieved through the links of negative self-image, illness comprehensibility and cognitive illness perceptions. These factors may serve as potential non-pharmaceutical action points to improve psychological and cognitive health among old PLWH. •Network analysis was used to estimate the interactions between psychology and cognition.•Psychological factors were intertwined with cognitive function in old people with HIV.•The network strength was stronger in subgroups with poorer psychological health.•Specific psychological factors may be action points for improving cognitive function.